JETT 2022
DOI: 10.47750/jett.2022.13.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Education innovations: new wartime experience of Ukrainian universities

Abstract: The study defines the significance of the development and support of educational innovation processes in Ukraine during the difficult period of Russian military aggression and determines the specifics of the introduction of pedagogical innovations in universities in wartime conditions. The classification of education innovations is highlighted, and several innovative approaches to the organization of distance/blended learning are presented. Using the results of the survey of Vasyl Stefanyk Precarpathian Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…At the same time, the authors' attempt to evaluate distance learning as a large-scale innovation seems quite debatable. In our opinion, the use of exclusively distance learning in the educational process during the war does not contribute to the solution of all educational tasks and depends on the influence of security factors [8].…”
Section: Introductionmentioning
confidence: 84%
“…At the same time, the authors' attempt to evaluate distance learning as a large-scale innovation seems quite debatable. In our opinion, the use of exclusively distance learning in the educational process during the war does not contribute to the solution of all educational tasks and depends on the influence of security factors [8].…”
Section: Introductionmentioning
confidence: 84%
“…The survey was conducted in April-May 2022, specifically during the initial months of the Russian-Ukrainian war. The questionnaires were created to reflect theoretical research on social support (Bezpalko, 2014;Semyhina, 2020), psycho-emotional support (Filonenko, 2008), and pedagogical support for war-affected persons (Budnyk, Kushniruk, Tsybulko, Shevchenko, Fomin, & Konovalchuk, 2022;Budnyk, & Sajdak-Burska, 2023). All survey participants were guaranteed anonymity.…”
Section: Instruments and Procedures Of Researchmentioning
confidence: 99%
“…remains relevant. The pandemic and war challenges in Ukraine have demonstrated that the use of digital technologies helps not only to intensify the learning process, increase its efficiency, and provide instant feedback but also to provide educational services even in crisis conditions (Budnyk, Kushniruk, Tsybulko, et al, 2022). The use of ICTs makes the teaching and research process more dynamic, personalized, and focused on individual abilities and personal potential.…”
Section: Features Of Professional Skills Development Of Future Primar...mentioning
confidence: 99%